2010
DOI: 10.1021/op100186c
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Development of an Efficient, Scalable, and Robust Route to the Novel CENP-E Inhibitor GSK923295A

Abstract: The discovery and development of an efficient manufacturing route to the CENP-E inhibitor 3-chloro-N-{(1S)-2-[(N,Ndimethylglycyl)amino]-1-[(4-{8-[(1S)-1-hydroxyethyl]imidazo[1,2-a]pyridin-2-yl}phenyl)methyl]ethyl}-4-[(1-methylethyl)oxy]benzamide (GSK923295A) is described. The existing route to GSK923295A was expensive, nonrobust, used nonideal reagents, and consistently struggled to deliver the API needed for clinical studies. The new synthesis commences from the readily available L-phenylalaninol, which is sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…To experimentally induce whole chromosome aneuploidies, we set out to synthesise the Cenp-E inhibitor, GSK923295 by following previously published routes [ 40 , 42 ]. A key step involves resolution of racemic 1-(2-amino-3-pyridinyl)ethanol (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To experimentally induce whole chromosome aneuploidies, we set out to synthesise the Cenp-E inhibitor, GSK923295 by following previously published routes [ 40 , 42 ]. A key step involves resolution of racemic 1-(2-amino-3-pyridinyl)ethanol (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The imidazo[1,2-a]pyridine scaffold, found at the core of many pharmaceutical drugs such as zolimidine ( peptic ulcer), 1 zolpidem (insomnia and brain disorders) 2 and rifaximin (hepatic encephalopathy), 3,4 is one of the most privileged nitrogencontaining heterocycles in drug design. [5][6][7][8] Industrial routes to imidazo [1,2-a]pyridines have often been via condensations between 2-aminopyridines and α-bromoketones/α-chloroketones (Scheme 1), 9,10 with an aryl or a carboxylate group at the β position for subsequent reduction to an OH group and derivatisation. [11][12][13] Recent synthetic methods have focused on functionalisation of the core scaffold through metal catalysed coupling reactions (e.g.…”
mentioning
confidence: 99%
“…An authentic sample of this material was readily accessible by reaction of 8 with sodium hydride in tetrahydrofuran and dimethylformamide to give a very good yield of 14 , further highlighting the risk of having excess potassium tert -butoxide within this process. The authors have observed this type of reactivity in a previous process; it is also reported for the base-mediated self-condensation of phenacyl halides, which is suggested to proceed via the intermediacy of an unsaturated dicarbonyl …”
Section: Results and Discussionmentioning
confidence: 53%